Progress of Acupuncture Therapy in Diseases Based on Magnetic Resonance Image Studies: A Literature Review - Zhang, Jinhuan; Li, Zihan; Li, Zhixian; Li, Jiaying; Hu, Qingmao; Xu, Jinping; Yu, Haibo (Frontiers in Human Neuroscience, 2021)
The neural mechanisms of acupuncture are not well understood. Over the past decades, an increasing number of studies have used magnetic resonance imaging (MRI) to investigate the brain's response to acupuncture. The current review aims to provide an update on acupuncture therapy in disease. The PubMed, Embase, Web of Science, and Cochrane Library databases were searched from inception to January 31, 2021. Article selection and data extraction were conducted by two review authors. A total of 107 publications about MRI in acupuncture were included, the collective findings of which were as follows: (1) Stroke and GB34 (Yanglingquan) are the most studied disease and acupoint. Related studies suggested that the mechanism of acupuncture treatment for stroke may involve modification of brain structure and function, balance between the left and right hemispheres, and activation of brain areas related to movement and cognition. GB34 is mainly used in stroke and Parkinson's disease, and its effects on the brain area occur mainly in the premotor cortex, the adjacent supplementary motor area, and the supramarginal gyrus; (2) Resting state functional MRI and functional connectivity (FC) analysis were the most frequently used approaches; (3) Estimates of efficacy and brain response to acupuncture depend on the type of sham acupuncture (SA) used for comparison. Brain processing after acupuncture differs between patients and healthy controls (HC) and occurs mainly in disorder-related areas. Factors which influence the effect of acupuncture including depth of needling, number and locations of acupoints, deqi and expectation effect, each contributing to the brain response. While studies using MRI have increased understanding of the mechanism underpinning the effects of acupuncture, there is scope for development in this field. Due to the small sample sizes and heterogeneous study designs and analytical methods, the results were not in agreement. Further studies with larger sample sizes, careful experimental design and multimodal neuroimaging techniques as well as standardized acupuncture and MRI methods should be conducted to better explain the efficacy and specificity of acupuncture, and to prepare for accurate efficacy prediction in the future.